解:(1)由已知f(-x)="-f(x)" 即log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517195540.png)
+log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517179525.png)
="0 " ………………………….1分
∴(1-mx)(1+mx)="(x+1)(1-x) " 1-m
2x
2=1-x
2 ∴m=
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517226190.png)
1 …………….3分
当m=1时,
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517179525.png)
=-1<0 舍去 ∴ m=-1 ……………….4分
(2)由(1)得f(x)=log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517257407.png)
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517273169.png)
任取1<x
1<x
2f(x
2)- f(x
1)= log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517288643.png)
- log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517304641.png)
= log
a
∵1<x
1<x
2 ∴(x
2+1)(x
1-1)-(x
2-1)(x
1+1)=2(x
1-x
2) ∴0<
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517319893.png)
<1
当a∈(0,1)时 log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517319893.png)
>0,∴f(x
2) > f(x
1),此时f(x)为增函数…7
当a∈(1,+∞)时 log
a![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517319893.png)
<0,∴f(x
2)< f(x
1) 此时为减函数。.8分
(3)有(2)知:当a>1时,f(x)在(1,+∞)为减函数
由
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517257407.png)
>0有x<-1或x>1∴(t,a)
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517397241.png)
(1,+∞) …………………………..9分
即f(x)在(t,a)上递减,∴f(a)="1," ∴a=1+
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517413336.png)
,且
![](http://thumb.zyjl.cn/pic2/upload/papers/20140823/20140823200517444395.png)
→+∞,∴t="1" ……………12分